Komunikasi Interpersonal Kepala Keluarga Berbasis Capacity Building Dalam Mencegah Kenakalan Remaja - Zuhriah, Zuhriah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
The phenomenon of juvenile delinquency occurs in almost every region in Indonesia. The current of globalization is the driving force for juvenile delinquency today. This condition is seen from the behavior of adolescents who often show apathetic and selfish attitudes and the surrounding environment. Outside the home teenagers also often take actions outside the bounds such as ditching school, drinking, brawl and gambling. The behavior reflects the lack of interpersonal communication that is built by parents in fostering their children and there is no specific strategy in preventing the behavior. The purpose of writing is to describe how interpersonal communication is applied by the head of the family based on capacity building. Capacity building is the process by which individuals and organizations acquire, improve and maintain the skills, knowledge, tools, equipment, and other resources needed to carry out their work competently. This allows the individual (head of the family) to attend to build interpersonal communication in a greater capacity in anticipating the involvement of their children in juvenile delinquency. In carrying out individual capacity building, measured through the concept of Gross namely decision making, communication, control.